The impact of change in the future composition of the international system - Hussein, Ali Abdel Karim (Tikrit Journal For Political Science, 2023)
There are quite a few ambiguities in most of the terminology and concepts in political science, and this applies very much to the concept of change that has filled the interest of researchers, as conflicting views on its indications and factors that produced the theoretical interest in the issue that led to the production of a large number of effects on the parties In the political, economic and social transformations that have taken place, the challenges and perspectives of changing it and the development of a new world order.